2016
DOI: 10.1080/09593330.2016.1183716
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium carbonate deposition on stainless steel using olive leaf extract as a green inhibitor

Abstract: The antiscale properties of the aqueous extract of olive (Olea europaea L.) leaves as a natural scale inhibitor for stainless steel surface in Hammam raw water were investigated using chronoamperometry (CA) and electrochemical impedance spectroscopy techniques in conjunction with a microscopic examination. The X-ray diffraction analysis reveals that the scale deposited over the pipe walls consists of pure CaCO calcite. The CA, in accordance with electrochemical impedance spectra and scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Such complexes prevent the deposition of calcium carbonate keeping calcium ions in the soluble form. According to GC-MS, phenolic derivatives such as pyrogallol, vanillic and gallic acids, eugenol, and polysaccharides are found in the extract [30][31][32]. e mechanisms for scale inhibition by the radish cake extract are associated with active functional groups (C�O, -OH, -COOH, and N�C�S groups) of the main compounds of the extract.…”
Section: Ermal Scaling Testmentioning
confidence: 99%
“…Such complexes prevent the deposition of calcium carbonate keeping calcium ions in the soluble form. According to GC-MS, phenolic derivatives such as pyrogallol, vanillic and gallic acids, eugenol, and polysaccharides are found in the extract [30][31][32]. e mechanisms for scale inhibition by the radish cake extract are associated with active functional groups (C�O, -OH, -COOH, and N�C�S groups) of the main compounds of the extract.…”
Section: Ermal Scaling Testmentioning
confidence: 99%
“…5). In the case of olive leaves extract, a concentration of 20 mg/L in the Hammam water was able to inhibit totally CaCO 3 coverage of the stainless steel electrode surface used in CA at 25°C (Aidoud et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to study the properties of quercetin solution towards CaCO 3 formation by using CA method and impedance measurements. Those properties could be compared to the results recently published elsewhere for natural extract (Aidoud et al, 2017) or green molecule (Karar et al, 2016) in similar conditions. The CaCO 3 crystals obtained during the experiments for the raw water and treated water with quercetin were characterized by SEM and X-ray diffraction (XRD) in order to get some insight into the inhibition mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain authors suggested that the fig leaf extract may complex the cations present in the brine solution, or to disperse the suspended solids through adsorption (Abdel‐Gaber et al ., 2011). Researchers have carried out the antiscale properties of the aqueous extract of olive leaves ( Olea europaea L.) for stainless steel surface in Hammam raw water (Aidoud et al ., 2017). Olive leaves contain many phenolic molecules including oleuropein, the most abundant biophenols in olive leaves (Bonoli et al ., 2004) and caffeic acid (Maciejewska et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%